PENGARUH PENGETAHUAN PAJAK, KESADARAN WAJIB PAJAK,TINGKAT PENGHASILAN, DAN SAKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB KENDARAN BERMOTOR PADA KANTOR SAMSAT SIDIKALANG - Marpaung, Thamrin; Saragih, Afni Eliana; Tampubolon, Herikson (Jurnal Ilmiah Akuntansi (JIMAT), 2023)
The purpose of this study was to determine the effect of tax knowledge, taxpayer awareness, level of income and tax sanctions on motor vehicle taxpayer compliance. This research was conducted at the Sidikalang Samsat. The number of samples in this study were 100 respondents with the sampling method using the method of collecting research data from the available set of respondents (convenience sampling). Data analysis techniques used in this research were descriptive statistics, data quality testing, multiple linear regression, classical assumption testing and hypothesis testing. Partial test results (t test) show that tax knowledge has a significant value of 0.029, taxpayer awareness has a significant value of 0.42, income level is 0.007, and tax sanctions are 0.000, which means it has a significant value <0.05. Based on the results of the analysis, it can be seen that tax knowledge, taxpayer awareness, income levels and tax sanctions have a significant effect on motor vehicle taxpayer compliance in the city of Sidikalang.Keywords : Tax Knowledge, Taxpayer Awareness, Income Level, Tax Sanctions